Distinct Mechanisms Regulate ATGL-Mediated Adipocyte Lipolysis by Lipid Droplet Coat Proteins - Yang, Xingyuan (Endocrine Society, 2013)
Adipose triglyceride lipase (ATGL) is the key triacylglycerol hydrolase in adipocytes. The precise mechanisms by which ATGL action is regulated by lipid droplet (LD) coat proteins and responds to hormonal stimulation are incompletely defined. By combining usage of loss- and gain-of-function approaches, we sought to determine the respective roles of perilipin 1 and fat-specific protein 27 (FSP27) in the control of ATGL-mediated lipolysis in adipocytes. Knockdown of endogenous perilipin 1 expression resulted in elevated basal lipolysis that was less responsive to β-adrenergic agonist isoproterenol. In comparison, depletion of FSP27 protein increased both basal and stimulated lipolysis with no significant impact on the overall response of cells to isoproterenol. In vitro assays showed that perilipin but not FSP27 was able to inhibit the triacylglycerol hydrolase activity of ATGL. Perilipin 1 also attenuated dose-dependent activation of ATGL by its Coactivator Comparative Gene identification-58. Accordingly, depletion of perilipin 1 and CGI-58 in adipocytes inversely affected basal lipolysis specifically mediated by overexpressed ATGL. Moreover, although depletion of perilipin 1 abolished the LD translocation of ATGL stimulated by isoproterenol, absence of FSP27 resulted in multilocularization of LDs along with increased LD presence of ATGL under both basal and stimulated conditions. Interestingly, knockdown of ATGL expression increased LD size and decreased LD number in FSP27-depeleted cells. Together, our results demonstrate that although FSP27 acts to constitutively limit the LD presence of ATGL, perilipin 1 plays an essential role in mediating the response of ATGL action to β-adrenergic hormones.